Drive Theory and Home Run Milestones in Baseball: An Historical Analysis. Issue 1 (February 2014) - Goldschmied, Nadav; Harris, Michael; Vira, Damien; Kowalczyk, Jason
The purpose of this investigation was to test whether the performance of the home run hitters in Major League Baseball adhered to predictions of Drive Theory. 24 baseball players who have hit at least 505 home runs were included in the sample. Their performance was assessed around the time in which they reached a significant home run career milestone, operationalized as either 500 or 600 home runs, or surpassing the league's home run record. As predicted, the players were found to require significantly more at-bats to complete the 5 home runs before the milestone, when stress was assumed to be mounting, than the 5 home runs after the milestone. In contrast, those players who reached the personal landmark from 1988 (the suspected commencement of the so-called "Steroid Era") onwards required the same number of at-bats before and after the milestone.